Tradisi Seribu Bubur Di Masjid Raya Al-Mashun Kota Medan - Laylan Supinah; Muhammad Nasihudin Ali; Muhammad Faishal (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study is to learn more about the "Tradition of a Thousand Porridge at the Al-Mashun Grand Mosque, Medan City," which is seen from a cultural perspective and focuses on local cuisine customs during the Makmun Al-Rasyid Perkasa Alamsyah Sultanate. The major goal of this essay is to demonstrate how the social life of the Malay community at Masjidi Raya Al-Mashun Medan is significantly influenced by regional cuisine. The three stages of the research procedures, or data collection techniques, are interview, observation, and documentation. The findings of this research are available in several ways regarding Sultan Makmun Al-Rasyid Perkasa Alamsyah in terms of the porridge tradition at the Al-Mashun Grand Mosque in Medan. Sultan is said to be a leader in his time for the former Malay community in the city of Medan. The Sultan in his time also had such great attention to the mosque building of this time. One of the mosques that has been successfully established is the Al-Mashun Grand Mosque in Medan, which is now the building still standing strong todat, and there are also several other mosques. The conclusion form this study can be drawn, that the traditional food traditions of these communities are closely related to their habits in everday life.